2020
DOI: 10.1096/fasebj.2020.34.s1.03176
|View full text |Cite
|
Sign up to set email alerts
|

Application of Kahoot! as a Teaching and Learning Tool in PharmD Curriculum

Abstract: Millennials approach things differently compared to earlier generations, and this includes the manner in which they learn. The absence of approaches best suited for teaching this generation can hinder their learning abilities. This can be particularly challenging in professional programs such as doctor of pharmacy where students are not only expected to have mastery of content but also demonstrate high level of knowledge retention. In recent years, there have been significant technological advances and an educ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 0 publications
1
7
0
Order By: Relevance
“…[21] Integrating a game-based tool, like Kahoot!, in learning can allow students to revise and apply what they have learned in an interactive, fun, and competitive way. [7] Enhancing gamebased learning can enhance medical students` engagement with Pathology and the findings of our study are consistent with the literature on digital games. [22] Learning methods and platforms that incorporate gamification as Web-based programs, mobile applications, and virtual patient simulations have proven successful in engaging students in learning activities.…”
supporting
confidence: 90%
See 1 more Smart Citation
“…[21] Integrating a game-based tool, like Kahoot!, in learning can allow students to revise and apply what they have learned in an interactive, fun, and competitive way. [7] Enhancing gamebased learning can enhance medical students` engagement with Pathology and the findings of our study are consistent with the literature on digital games. [22] Learning methods and platforms that incorporate gamification as Web-based programs, mobile applications, and virtual patient simulations have proven successful in engaging students in learning activities.…”
supporting
confidence: 90%
“…It can be utilized inside or outside the classroom for individual students` asynchronous practice or synchronous students` challenges. [4,[7][8][9] Quizzes can be created freely on the platform by create quiz, then selecting the type of the question (MCQ, or true/false), writing it, followed by choosing the assigned time in seconds for each question. The platform asks you to mark the correct answer to be presented to the students when they answer each question as a feedback.…”
Section: Introductionmentioning
confidence: 99%
“…Integrating a game-based tool in learning can allow students to revise and apply what they have learned in an interactive, fun, and competitive way [11]. Enhancing game-based learning can enhance medical students` engagement with Pathology and the findings of our study on like Kahoot!…”
Section: Discussionmentioning
confidence: 81%
“…It can be utilized inside or outside the classroom for individual students` asynchronous practice or synchronous students` challenges. [8,[11][12][13] Quizzes can be created freely on the platform. The instructor selects "create quiz," then the type of the question he/she plans to create (MCQ, or true/false).…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, Ali et al also established that incorporation of interactive polls in oral pathology lectures through user friendly tools was gratifying for the students. ( 25) Similarly a study conducted by Ofori et al on application of polling technology in PharmD course demonstrated that around 84% survey respondents believed this interaction to be enjoyable and exciting (29). Many authors have illustrated an optimistic shift in the traditional classroom setting after introduction of game-based quizzes in teaching.…”
Section: Discussionmentioning
confidence: 99%